Rancang Bangun Aplikasi Mobile Pengenalan Huruf Jawa (Aksara Jawa) Berbasis Android - Indah Puji Astuti; Ega Feri Romawati; Ida Widaningrum (Universitas Muhammadiyah Riau, 2020)
Technological developments, especially smart phones, have been widely applied in the education sector. One example is the number of mobile-based learning media. Javanese language, especially Javanese script, has begun to erode because it is very rare nowadays to learn Javanese. The many forms of writing and also terms in Javanese script sometimes make us lazy and reluctant to learn them. In this study, the authors made an application as an Android-based learning media for learning Javanese characters. The application is equipped with a voice reading character so that users can easily understand the material. In addition, the application is equipped with a quiz to review the user's ability to learn Javanese script. Android based was chosen because the smart phone owned in addition to communication media can also be used for learning media. This research uses the waterfall system method. The stages used are analysis, design, coding and testing. The results of the black box testing on this application show that the application is running well according to its function.